The Ego Identity Creating for the Secondary School Students at Fourth Grade - Dr. Abdil-Karim Atta Kareem; Mary Hussny Khayon (Migration Letters, 2023)
The following are the objectives of the current study to know: How to create one’s ego identity for the Secondary School Students at Fourth Grade. To know how to create ego identity in accordance with differences in gender (male and female). To know how to create ego identity in accordance with specialty (literary and scientific). The two researchers have made a scale to create Ego Identity included (40) distributed over three variables. They used a final sample of (363) students from the fourth grade of a secondary school (214 males and 9149 girls), who were randomly selected from the Thi-Qar school of the province center. Ten of the paragraphs have undergone logical and statistical analysis to determine their distinct capacity and proper coefficient. For confirming the research measure and results, the researchers have demonstrated their artificial correctness, markers of scale building correctness, and calculated scale capability using the Ron Bach equation (internal reliability) and the mess of test (external reliability). Test for two independent samples and the person coefficient (T test for one sample) The outcomes result in The study sample used to develop ego identity: According to the gnder9 male-female) for the sake of females, there is statistical variation at the level of coefficient (0,05) for the scale to construct ego identification to the research sample.